Implementasi Praktik Baik Perikanan Tangkap Berkelanjutan di Kecamatan Ayah Kabupaten Kebumen - Tri Wiji Nurani; Prihatin Ika Wahyuningrum; Rianti Dyah Hapsari; Nurani Khoerunnisa; Elvanri Anggi Widianti; Eko Sri Wiyono; Iin Solihin; Muhammad Dahri Iskanda; Sugeng Hari Wisudo (Institut Pertanian Bogor, 2023)
Fish Landing Bases Pasir, Karangduwur, and Argopeni are centers of fishing activities in Ayah District Kebumen Regency. Most fisher have limited knowledge related to the sustainability of fish resources, environmentally friendly fishing technology, good fish handling, and business management. Community service activities for Lecturers Returning to Kampung IPB are carried out to increase the capabilities of fishers in Kebumen Regency through the implementation of good practices in sustainable capture fisheries. Activities are carried out in three stages, namely: 1) Exploration of issues and problems; 2) Program implementation; and 3) Follow-up. The results of the activity show that the deepening of issues and problems becomes the basis for focusing on the preparation of implementation materials. Dissemination and discussions have been effective in increasing stakeholders' understanding of good practices in sustainable capture fisheries. As a follow-up activity, fishermen's capabilities need to be continuously improved in terms of catching lobsters that are already fit for catching, doing good fish handling for export commodity fish starting from the catching process to marketing distribution, processing abundant fish during the fish season, as well as effective business and financial management to address to the presence of seasonal fish.